Morphing euphoria a hybrid architecture aiding in the deterrence of adolescents from drugs use - Vahabzadeh, Yasemin (My University, 2018)
The social issue of substance use disorder, predominantly amongst the youth, has proven to be one of the rifest in the world, particularly within the South African context. This issue has taken over 15% of South Africa’s population. The Rosettenville community is a historically prominent community with a recent drug epidemic. Therefore using this community this research report explores, through design principles and typologies, how to create a hybrid architecture which incorporates a youth centre and a safe house to aid in the deterrence of adolescents from drug use. This research report discusses an architectural response that is directly linked to the way in which drugs deteriorate the user. Just as drugs eat away from a person both emotionally and physically, the designed building eats into the flat landscape of the chosen site. Once the user acknowledges their issues and wants to regain purpose of their lives they will begin to rebuild themselves. However, they will never return to their original state, and so the building speaks the same language of intentionally cutting into the landscape and building up from those foundations. This gives both the general public and individuals with drug use disorder a purpose in all the building aspects.